Os desafios na gestão dos recursos hídricos e os comitês de bacias hidrográficas no estado do Amazonas - Quadros, Jefferson Rodrigues De (2015)
The multiple uses and interests on waters have revealed a worrying context of scarcity and water pollution. The unequal distribution and inadequate use have produced conflicts and put into question the guarantee of this resource for present and future generations. Modify this context and establish agreements between the various uses require institutional arrangements capable of reconciling the various interests and the collective production of solutions, which necessarily passes through the enviromental law, while human science endowed with interdisciplinary capacity to dialogue with other branches of science. In this sense, and in order to contribute to solving this problem, international law were establishing and conferences were held that culminated in producing policy guidelines that guided the Brazilian legislation on water management , in particular, by law 9.433 / 97. Among the water management tools employed by the Brazilian standard the creation the Hydrographic Basin Committees as an expression of the principle of participation and as a legal instrument to assist in the management of water resources programs, being a collegiate body of participation and integration between government , users and society to the decision-making on how to conduct the management of water resources. And here lies the core of the research: the Hydrographic Basin Committees and the challenge of implementation of its statutory duties. Considered that the creation of Hydrographic Basin Committees endowed with institutional strength and financial autonomy to fulfill their duties represent the embryo for the realization of a participatory and efficient water management policy, and converging such a design/ concept to the existing factual context in Amazonas State for the management of its water resources, the theme of this research came. Thus, the timely topic of the dissertation deals with the Water Law, specifically in relation to the challenges for the management of water resources in the State of Amazonas, especially in relation to the Committees of Basin Tarumã-Açu River and the Rio Puraquequara, located around the city of Manaus, from the difficulties encountered in the implementation of their management. Thus, the overall objective of the study is to analyze the challenges to be faced to the Committees as essential instrument for the management of water resources, will fulfill its legal duties in the state of Amazonas, for the construction of proposals from the difficulties encountered in the implementation of their management. With the aim of guiding the study, we used the method, qualitative, descriptive, application, deductive, extract from official public sources, from legislation, from scientific and doctrinal papers and developed field research.